Anti‐diabetic and neuroprotective effects of pancreatic islet transplantation into the central nervous system. Issue 1 (23rd April 2015) - Lazard, Daniel; Vardi, Pnina; Bloch, Konstantin
Summary: During the last decades, the central nervous system (CNS) was intensively tested as a site for islet transplantation in different animal models of diabetes. Immunoprivilege properties of intracranial and intrathecal sites were found to delay and reduce rejection of transplanted allo‐islets and xeno‐islets, especially in the form of dispersed single cells. Insulin released from islets grafted in CNS was shown to cross the blood–brain barrier and to act as a regulator of peripheral glucose metabolism. In diabetic animals, sufficient nutrition and oxygen supply to islets grafted in the CNS provide adequate insulin response to increase glucose level resulting in rapid normoglycemia. In addition to insulin, pancreatic islets produce and secrete several other hormones, as well as neurotrophic and angiogenic factors with potential neuroprotective properties. Recent experimental studies and clinical trials provide a strong support for delivery of islet‐derived macromolecules to CNS as a promising strategy to treat various brain disorders. This review article focuses mainly on analysis of current status of intracranial and intrathecal islet transplantations for treatment of experimental diabetes and discusses the possible neuroprotective properties of grafted islets into CNS as a novel therapeutic approach to brain disorders with cognitive dysfunctions characterized by impaired brain insulin signalling. Copyright © 2015 John Wiley & Sons, Ltd.